Targeting Endothelial Barrier Dysfunction Caused by Circulating Bacterial and Mitochondrial N-Formyl Peptides With Deformylase - Martinez-Quinones, Patricia; Komic, Amel; McCarthy, Cameron G.; Webb, R. Clinton; Wenceslau, Camilla Ferreira (Frontiers in Immunology, 2019)
Despite recent advances in our understanding of the mechanisms underlying systemic inflammatory response syndrome (SIRS) and sepsis, the current therapeutic approach to these critically ill patients is centered around supportive care including fluid resuscitation, vasopressors and source control. The incidence of SIRS and sepsis continues to increase in the United States and patients die due to failure to respond to the traditional therapies of nitric oxide blockade, adrenergic agonists, etc. Bacterial and mitochondrial N-formyl peptides (NFPs) act as damage-associated molecular patterns and activate the innate immune system through formyl peptide receptors (FPR) located in immune and non-immune cells, including the vascular endothelium. The resulting inflammatory response manifests as capillary leak, tissue hypoperfusion and vasoplegia, partially due to endothelium barrier breakdown. Potential strategies to prevent this response include decreasing NFP release, breakdown of NFPs, and blocking NFPs from binding FPR. We propose the use of deformylase, the degrading enzyme for NFPs, as potential therapeutic approach to prevent the deleterious effects of NFPs in SIRS and sepsis.